Polycystic Ovary Syndrome Is a Challenging Problem in Women - Hassan, Arifa; Muzaffar, Muzamil; Reshi, Afshana Bashir; ., Arooj; Rafi Reshi, Mohd; Naqvi, Maaz (Asian Journal of Pharmaceutical Research and Development, 2023)
A diverse endocrine condition, polycystic ovarian syndrome is characterised by ovarian cysts, anovulation, and endocrine variance in women. As from the World Health Organisation, PCOS affects more than 116 million women globally. Patients with irregular periods and clinical indications of hyperandrogenism, such as acne, seborrhea, hirsutism, irregular menses, infertility, and alopecia, are suspected of having polycystic ovarian syndrome, a "multispeciality" illness. It is now widely acknowledged that oxidative stress plays a crucial part in the pathogenesis of numerous illnesses, including PCOS. OS is thought to have close interactions with PCOS characteristics, including insulin resistance (IR), hyperandrogenemia, and chronic inflammation. Although highly complicated antioxidant enzyme and non-enzymatic systems regulate intracellular reactive oxygen species formation and propagation, knowing the mechanisms that underlie oxidative stress is crucial to the development of PCOS prevention and treatment options. Management should prioritise encouraging employees, educating the public, resolving psychological issues, and highlighting a healthy lifestyle with appropriate medical treatment. Long-term metabolic problems need to be monitored and managed as part of standard therapeutic care. To help with early diagnosis, appropriate investigation, routine screening, and treatment of this common illness, comprehensive evidence-based guidelines are required. The research suggests that phytoestrogen rich herbal extracts reduce hyperandrogenism, insulin resistance, and ovarian weight while increasing ovulation. As a result, these plants may have some effect on the levels of various hormones in the serum as well as ovarian weight and morphology, which presents a chance to research and find novel bioactive compounds.